2019
DOI: 10.25186/cs.v14i3.1577
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Fluazifop-P-Butyl in Young Coffee Plants

Abstract: Weed control is fundamental in coffee cultivation due to their big interference, competing with the crop for water, light and nutrients. Among the control methods used, chemical control is highlighted, as a function of its high efficiency and low cost. However, due to application failures, herbicide drift phytotoxicity is common. Aiming at the search for selective active ingredients in coffee plants, the objective of this study was to evaluate the selectivity of the active ingredient Fluazifop-p-butyl in young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…As well as the symptoms of phytotoxicity, the time factor is also crucial for observing changes in anatomical leaf characteristics in coffee plants submitted to herbicide application. In this work, changes in anatomical leaf characteristics were identified at 65 DAA, despite that, Voltolini et al (2019) and Castanheira et al (2019a) did not find influence of these characteristics at 120 DAA of the herbicides fluazifop-p-butyl and chlorimuron-ethyl respectively.…”
Section: Anatomical Featurescontrasting
confidence: 54%
See 1 more Smart Citation
“…As well as the symptoms of phytotoxicity, the time factor is also crucial for observing changes in anatomical leaf characteristics in coffee plants submitted to herbicide application. In this work, changes in anatomical leaf characteristics were identified at 65 DAA, despite that, Voltolini et al (2019) and Castanheira et al (2019a) did not find influence of these characteristics at 120 DAA of the herbicides fluazifop-p-butyl and chlorimuron-ethyl respectively.…”
Section: Anatomical Featurescontrasting
confidence: 54%
“…Acetyl-CoA carboxylase (ACCase) inhibiting herbicides appear as an alternative to glyphosate, which is a non-selective full-action herbicide for coffee trees, as well as the possibility of association with ALS-inhibiting herbicides. In this context, Castanheira et al (2019a) and Voltolini et al (2019) observed that the herbicides chlorimuronethyl (ALS) and fluazifop-p-butyl (ACCase) did not cause significant changes in growth and physiological characteristics and morphological characteristics of coffee seedlings even submitted to high doses of these herbicides.…”
Section: Introductionmentioning
confidence: 99%